Korean Language Education in Australian Schools - Anderson, K.; Cho, Y.; Choi, K.; Elfving-Hwang, Jo; Gillingham, E.; Honeywood, P.; Hughes, K.; Kwon, J.; Peters, K.; Pitt, J.; Star, S.; Street, L.; et al. (2023)
Foreword This follow-up report to IEAA’s ‘National Symposium on the future of Australia-Korea school partnerships’ serves to share key learnings, ensure accessibility and deepen impact of the information and insights that were presented during the symposium. Held over 29 August, 30 August and 1 September 2023, the symposium brought together more than 240 school leaders, educators, policy makers and a diverse range of other school stakeholders from both Australia and Korea. These included representatives from Australia’s Department of Education, Seoul Metropolitan Office of Education, Korean Education Centre, Austrade, Asia Education Foundation, Australia-Korea Business Council and Australian state and territory based Departments of Education and study clusters. Over three days, participants heard from a range of expert speakers regarding existing models for Australia-Korea school partnerships, Korean language education in Australia, case studies of recent innovative Australia-Korea school partnerships and government priorities for the future of bilateral school partnerships. Our symposium was a unique learning opportunity for attendees as AustraliaKorea school partnerships are often not explored in-depth through other international education fora. On behalf of IEAA, I extend my gratitude to symposium attendees, speakers and hosts for contributing to this milestone event. I also acknowledge the support of the Australia-Korea Foundation grants program, which facilitated the design and delivery of this National Symposium. The International Education Association of Australia is Australia’s leading association for international education. We strive to empower professionals, engage institutions and enhance Australia’s reputation as a provider of world-class education. We provide advocacy and member services relevant to professional staff, academics and teachers across all sectors, including schools. IEAA delivers high-quality professional learning – such as the National Symposium on the future of Australia-Korea school partnerships – to advance members’ careers and enhance the quality of Australian international education. Through this symposium, and our successful Australia-Korea Foundation grant which supported it, IEAA celebrates the work of our members and other stakeholders who work in and with schools. One of the most important aspects of school partnerships are the people-to-people connections which they seed. For students, when this occurs during their formative years, they become a catalyst for life-long bilateral connections and contribute to closer, stronger relationships between Australia and Korea. This highlights the significance of school partnerships within the broader context of international education. Hon. Phil Honeywood CEO, IEAA